PRODUCTION AND GRASS QUALITY HYMENACHNE AMPLEXICAULIS (RUDGE) NEES AT VARIOUS LEVELS OF BIOURINE FERTILIZATION AND ARBUSCULAR MYCORRHIZAL FUNGI - Syafria, Hardi (SENTRI: Jurnal Riset Ilmiah, 2024)
The research aims to determine and study the effects of giving biourine and Arbuscular Mycorrhizal Fungi (AMF) on the production and quality of Hymenachne amplexicaulis (Rudge) Nees grass in former coal mining land. The research was carried out in a Randomized Block Design, with six treatments and three replications. Treatment consisted of: (A) Biourine 0% + AMF 0 g/clump, (B) Biourine 0% + AMF 20 g/clump, (C) Biourine 30% + AMF 0 g/clump, (D) Biourine 30% + FMA 20 g/clump, (E) Biourine 45% + FMA 0 g/clump, (F) Biourine 45% + AMF 20 g/clump. The variables observed were the cumulative production of forage dry matter, crude protein and phosphorus content. The results showed that the treatment had a significant effect on the cumulative production of dry matter, crude protein and phosphorus. The biourine treatment of 45% + AMF 20 g/clump resulted in a cumulative production of forage dry matter (2373.61 kg/ha), crude protein content (15.56%) and phosphorus (1.17%) higher than other treatments.